Carboplatin plus etoposide in heavily pretreated castration-resistant prostate cancer patients. (June 2014) - Buonerba, Carlo; Federico, Piera; Bosso, Davide; Puglia, Livio; Policastro, Tania; Izzo, Michela; Perri, Francesco; Vittoria Scarpati, Giuseppina Della; Ferro, Matteo; Cobelli, Ottavio De; Placido, Sabino De; Aieta, Michele; et al.
ABSTRACT: : Aims: Carboplatin plus etoposide has modest efficacy in docetaxel-pretreated castration-resistant prostate cancer patients. We hypothesized that carboplatin–etoposide could still exert some therapeutic activity after docetaxel, cabazitaxel and either abiraterone or enzalutamide.Patients & methods: We enrolled 15 patients in the first step of a Phase II trial. The target sample size is 46 patients. The primary end point of the study was progression-free survival after 12 weeks.Results: The median progression-free survival was 11 weeks (range: 8–18), while median overall survival was 18 weeks (range: 12–26). Of seven patients with measurable disease, two had a partial response, two showed stable disease and the remaining three had progressive disease as the best radiological response. Five patients were considered progression-free after 12 weeks, prompting continuation of the trial.Conclusion: Our preliminary findings support the hypothesis that carboplatin plus etoposide may yield some clinical benefit in a population of patients who failed all currently approved therapeutic options for prostate cancer.